The Antinomic Method of Gregory Palamas: Between Transcendence and Immanence, God’s Essence and Energy, Single and Multiple Trinity - Zhukovskyy, Viktor (Verbum Vitae, 2023)
The article examines the theological method of antinomy and the conceptual solution to the problem of the ontological “gap” between transcendence and immanence of the Holy Trinity in the theological thought of the outstanding Byzantine theologian of the 14th century Gregory Palamas. The article analyzes how Palamas, in his patristic teaching on the distinction between the essence and energy of the Holy Trinity, substantiates the unity, trinity, and multiplicity of divine action in the world, and how he interprets this distinction in God’s nature. Particular attention is paid to biblical and patristic analysis and the significance of Palama’s methodological “triangle”: apophatic, cataphatic, antinomy; his understanding of the personal dimension of the energies of the hypostases of the Trinity, and the problem of the “simplicity” of the Triune God.